CB1 cannabinoid receptor agonist inhibits matrix metalloproteinase activity in spinal cord injury: A possible mechanism of improved recovery. (15th June 2015) - Hong, Jun; Nandiwada, Vijaya; Jones, Victoria; Lu, Miaomiao; Warner, David S.; Mukhopadhyay, Somnath; Sheng, Huaxin
Highlights: We examined the effect of a selective CB1R agonist, ACEA in mouse spinal cord injury model. ACEA significantly improved functional deficit and reduced the compression lesion volume. MMP-9 activity was increased in SCI and inhibited by ACEA. The effect of ACEA on MMP-9 activity was abolished by CB1R, but not CB2R antagonism. Abstract: Increased matrix metalloproteinase (MMP) activity contributes to glial scar formation that inhibits the repair path after spinal cord injury (SCI). We examined whether treatment with N -​(2-​chloroethyl)-​5Z, ​8Z, ​11Z, ​14Z-​eicosatetraenamide (ACEA), a selective synthetic cannabinoid receptor (CB1R) agonist, inhibits MMP and improves functional and histological recovery in a mouse spinal cord compression injury model. Injured mice randomly received either intraperitoneal ACEA (3 mg/kg/day) or vehicle for up to 3 weeks. Behavioral, histological and biochemical assays were performed. Rotarod assessment and the Basso Mouse Scale score showed an improved performance following ACEA treatment concomitant with a decrease in compression lesion volume. MMP-9 and MMP-2 activity was measured at 1, 7 and 14 days post-SCI. SCI markedly increased MMP-9, but had negligible effect on MMP-2 activity. ACEA-treatment decreased MMP-9 activity by 80%, 49%, and 56%, respectively ( P  < 0.05) and had a smaller effect on MMP-2 activity. The CB1R antagonist SR141716, but not the CB2R antagonist SR144528, blocked ACEA-mediated decrease in MMP-9 activity confirming the role of the CB1R in the process. Collectively these data demonstrate that post-injury CB1R agonism can improve SCI outcome and also indicate marked attenuation of MMP-9 proteolytic enzyme activity as a biochemical mechanism.